2009
DOI: 10.1109/tmi.2009.2018622
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Mirror: A New Interaction Paradigm for Augmented Reality Environments

Abstract: Medical augmented reality (AR) has been widely discussed within the medical imaging as well as computer aided surgery communities. Different systems for exemplary medical applications have been proposed. Some of them produced promising results. One major issue still hindering AR technology to be regularly used in medical applications is the interaction between physician and the superimposed 3-D virtual data. Classical interaction paradigms, for instance with keyboard and mouse, to interact with visualized medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 38 publications
0
58
0
Order By: Relevance
“…4,10 The results of the current study showed the error of the needle angle to be 0.96° in the axial plane when using a spine phantom. These experimental results were, however, measured 1.09 ± 0.78 ‡ * p < 0.01; EIA for both groups (without VIPAR vs with VIPAR; n = 10) and both operators were analyzed with Tukey test.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…4,10 The results of the current study showed the error of the needle angle to be 0.96° in the axial plane when using a spine phantom. These experimental results were, however, measured 1.09 ± 0.78 ‡ * p < 0.01; EIA for both groups (without VIPAR vs with VIPAR; n = 10) and both operators were analyzed with Tukey test.…”
Section: Discussionmentioning
confidence: 62%
“…If AR technology was applied to navigation surgery such as spinal instrumentation placement or tumor resection, it could overcome the problem of current navigation systems that require the surgeon to deal with multiple areas of attention, the surgical site, and the display of the navigation system during the navigation task. 4 Furthermore, an AR system with a HMD can provide 3D information from any angle that the surgeon requires simply by moving the surgeon's head, and it can also provide a different augmented navigational view for each surgeon wearing an HMD. Augmented-reality guidance technology can also streamline the workflow of cumbersome spinal surgeries by allowing necessary medical data to be shared with each operator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mirror was successfully tested with a phantom, a cadaver, and a patient. At that time, however, we have not evaluated its usefulness for any kind of application [2]. This first generation of the virtual mirror has been presented to 20 surgeons within the scope of an earlier study [20] that assessed the perception of different methods of in-situ visualization.…”
Section: Studying the Benefit Of Virtual Mirrors For Medical Applicatmentioning
confidence: 99%
“…Finally, interaction models include both traditional computer-based controls and body mounted sensors or even more complex physical haptics. Recent approaches include wearable gestural interfaces [15], tangible interfaces [16] and virtual mirrors [17]. In this paper we develop a setup for projection-based augmented maps that is based on a projective-invariant marker design which is used for four different purposes: the detection of the physical controller moved by the user, the localization in the 3D space of the display surface and, finally, the calibration of both the camera and the projector.…”
Section: Introductionmentioning
confidence: 99%